(untitled) (Philological Studies, 2019)
Dialectology is a branch of linguistics that deals with the studying of certain language dialects. Dialectology’s task is to detect and study the laws of the origin of dialects and follow their development. The subject of analysis of this article is the speech in village Siricino, the region of Tetovo. The article attempts a complete picture of this speech on the phonological, morphological, syntactic, lexical and onomastic levels. Looking at the big picture, the speech in this village is a typical North-West dialect, while some parts of its features differ from the speech typical in Tetovo, but more from the speech in Vratnica (a neighboring village), so that the study of this speech gives us an overall picture regarding the distribution of the dialect’s features in the territory of Dolni Polog, especially in terms of the isoglosses of certain dialect features.